2007
DOI: 10.1111/j.1460-9568.2007.05929.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of dopamine homeostasis underlies selective neurodegeneration mediated by α‐synuclein

Abstract: A key challenge in Parkinson's disease research is to understand mechanisms underlying selective degeneration of dopaminergic neurons mediated by genetic factors such as alpha-synuclein (alpha-Syn). The present study examined whether dopamine (DA)-dependent oxidative stress underlies alpha-Syn-mediated neurodegeneration using Drosophila primary neuronal cultures. Green fluorescent protein (GFP) was used to identify live dopaminergic neurons in primary cultures prepared on a marked photoetched coverslip, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 44 publications
8
48
1
Order By: Relevance
“…Previous work has shown that the expression of human ␣-synuclein in primary neuronal cultures from Drosophila embryos induces a progressive and selective loss of dopamine neurons over a period of several days (Park and Lee, 2006;Park et al, 2007). However, we found that supplementing the culture media with either a coffee extract or a tobacco extract completely suppressed the loss of THpositive neurons induced by ␣-synuclein expression in this cell culture system (Fig.…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous work has shown that the expression of human ␣-synuclein in primary neuronal cultures from Drosophila embryos induces a progressive and selective loss of dopamine neurons over a period of several days (Park and Lee, 2006;Park et al, 2007). However, we found that supplementing the culture media with either a coffee extract or a tobacco extract completely suppressed the loss of THpositive neurons induced by ␣-synuclein expression in this cell culture system (Fig.…”
Section: Resultscontrasting
confidence: 46%
“…Primary neuron culture. Primary DA neuron cultures were prepared as described previously (Park and Lee, 2006;Park et al, 2007) and grown for 3 d. Decaffeinated coffee and nicotine-free tobacco extracts were added to cultures at a final dilution of 1:2000. After 6 d of exposure to coffee and tobacco extracts, DA neurons were detected and quantified relative to 4Ј,6Ј-diamidino-2-phenylindole-positive cells, as described previously (Park and Lee, 2006;Park et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, early reports demonstrated that oxidative conditions in vitro [153] and in cultured cells [154] promote α-synuclein aggregation to amyloid-like structures. Moreover, using primary neurons from transgenic Drosophila expressing A30P mutant α-synuclein, it was shown that lessening dopamine-dependent oxidative stress with glutathione treatment or by sequestering dopamine in vesicles reduced toxicity [155]. In addition to iron, metals such as and copper, calcium, aluminum, and zinc have been shown to promote α-synuclein aggregation, perhaps by neutralizing the negative C-terminal charge, thereby promoting a partially folded amyloidogenic intermediate [156,157], or through other redox-dependent interactions.…”
Section: Oxidation and Nitrationmentioning
confidence: 99%
“…DJ-1 and dLRRK function seem to provide essential protection against oxidative stress also in Drosophila but the mechanisms involved remain to be elucidated (dashed arrow represents possible association with mitochondria). Elevating the levels of glutathione-S-transferase or SOD protects DA neurons in parkin mutants or in a-synuclein-expressing flies suggesting a central role of oxidative stress in those fly models for PD a-synuclein (Park et al 2007). Therefore, the increased toxicity of a-synuclein seen in flies under hyperoxia might be due to an accelerated auto-oxidation of dopamine, a process that normally takes place slowly during ageing under normal oxygen conditions.…”
Section: Drosophila Models Reveal Oxidative Stress As a Key Element Imentioning
confidence: 97%
“…Second, in different experiments aimed to counteract oxidative damage on a-synuclein transgenic flies, both, the histological and the locomotor phenotypes could be rescued (Feany and Bender;2000;Yang et al 2003;Pendleton et al 2002;Wassef et al 2007;Botella et al 2008). Third, Park et al (2007) have assessed the toxicity of a-synuclein using Drosophila primary neuronal cultures in an in vitro model for PD. In this work, the decrease in GFP intensity of traced cultivated neurons was used as a sign of neurodegeneration.…”
Section: Da Neuronal Loss In Drosophila Models: An Apparent Controversy?mentioning
confidence: 98%